A New Dihydrobenzofuran Neolignan from Stem of Flue-Cured Tobacco and its Anti-tobacco Mosaic Virus Activity - Zhang, Tao; Shen, Qinpeng; Liu, Chunbo; Zhang, Fengmei; He, Pei; Wang, Kunmiao; Zhu, Ruizhi; Yang, Guangyu; Liu, Zhihua (Asian Journal of Chemistry, 2015)
A new dihydrobenzofuran neolignan, tobdihydrofuran A (1), was isolated from the stems of flue-cured tobacco (a variety of Nicotiana tabacum L). Its structure was elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compound 1 was also tested for its anti-tobacco mosaic virus (anti-TMV) activity and it shows potential anti-tobacco mosaic virus activity with inhibition rates of 28.6 %.